Plasma Aldosterone Concentration Is Positively Associated With Pulse Pressure in Patients With Primary Hypertension. Issue 10 (March 2015) - Yao, Xiaoguang; Li, Nanfang; Zhang, Yujie; Zhang, Juhong; Abulikm, Suofeiya; Zhang, Delian; Chang, Guijuan; Zhou, Keming; Kong, Jianqiong; Lymperopoulos., Anastasios
<x xml:space="preserve">Abstract</x> Abstract Increasing evidence showed a link between arterial elasticity and stiffness and pulse pressure (PP), in which plasma aldosterone may play a role. The observational study aimed to explore the potential relations between plasma aldosterone concentration (PAC) and PP in patients with hypertension. We evaluated the relation between PP and PAC in supine, seated, and upright positions in 195 patients with primary hypertension who underwent postural stimulation test. They were divided into 3 groups by tertiles of PP: PP ⩽ 44 mm Hg (n = 70), 44 mm Hg < PP ⩽ 51 mm Hg (n = 63), and PP ≥ 51 mm Hg (n = 62). The PAC in different postures was compared, respectively. The results showed the following. First, segregated by tertiles of PP, serum K+, 24-hour systolic blood pressure, 24-hour diastolic blood pressure, sex, upright PAC, and seated PAC showed statistically significant differences in groups. Second, the PAC were significantly different in 3 levels of PP regardless of postures, the individuals with PP ≥ 51 mm Hg had the highest PAC. On contrast, the patients with PAC > 12 ng/dL showed greater PP than those with PAC ⩽ 12 ng/dL. Third, weak associations between PP and upright (r = 0.288, P < 0.001), seated (r = 0.265, P < 0.001), and supine postures (r = 0.191, P = 0.008) were detected by simple correlation analysis. After corrected serum K+, age, and sex, the partial correlation coefficients did not change greatly. Fourth, the logistic regression model was constructed with PP ≥ 40 mm Hg or PP < 40 mm Hg as the dependent variable; the serum K+[OR = 0.043, 95% CI: 1.09(1.00–1.12)] and PAC [OR = 0.025, 95%CI: 0.35(0.13–0.88)] were included as significant contributing factors. The results showed that higher PAC was weakly, but significantly, correlated to greater PP regardless of different postures, suggesting that higher PAC may be a risk factor of reduced arterial elasticity in patients with hypertension.